1995
DOI: 10.1128/mcb.15.9.5152
|View full text |Cite
|
Sign up to set email alerts
|

FER-1, an Enhancer of the Ferritin H Gene and a Target of E1A-Mediated Transcriptional Repression

Abstract: In addition, gel retardation assays showed that E1A reduces the ability of nuclear proteins to bind to the AP1-like sequence without affecting the levels of nuclear factors that recognize the 22-bp dyad symmetry element. Taken together, these results demonstrate that FER-1 serves as both an enhancer of ferritin H transcription and a target for E1A-mediated repression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 52 publications
5
76
0
Order By: Relevance
“…It should be noted that we confirmed previous reports by Costanzo and colleagues (Bevilacqua et al, 1997; Oxidative stress and the human ferritin H gene Y Tsuji Faniello et al, 1999) and Battistini and colleagues (Marziali et al, 1997) that the proximal region containing CCAAT box is involved in basal expression of the human ferritin H gene because we observed that the À0.15 kb region has much higher luciferase expression than that driven by À0.03 kb region containing only TATA box of the ferritin H gene (Figure 2). Beaumont et al (1994) and our previous mouse ferritin H studies (Tsuji et al, 1995) demonstrated that the major basal enhancer element (we initially characterized it as a target of the adenovirus E1A oncogene for transcriptional repression; (Tsuji et al, 1995) is located approximately 4.1 kb upstream from transcription initiation site in the mouse ferritin H gene. We then identified that the E1A-targeted basal enhancer element, JunD expression in nucleus and phosphorylation at Ser100 during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that we confirmed previous reports by Costanzo and colleagues (Bevilacqua et al, 1997; Oxidative stress and the human ferritin H gene Y Tsuji Faniello et al, 1999) and Battistini and colleagues (Marziali et al, 1997) that the proximal region containing CCAAT box is involved in basal expression of the human ferritin H gene because we observed that the À0.15 kb region has much higher luciferase expression than that driven by À0.03 kb region containing only TATA box of the ferritin H gene (Figure 2). Beaumont et al (1994) and our previous mouse ferritin H studies (Tsuji et al, 1995) demonstrated that the major basal enhancer element (we initially characterized it as a target of the adenovirus E1A oncogene for transcriptional repression; (Tsuji et al, 1995) is located approximately 4.1 kb upstream from transcription initiation site in the mouse ferritin H gene. We then identified that the E1A-targeted basal enhancer element, JunD expression in nucleus and phosphorylation at Ser100 during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and the human ferritin H gene Y Tsuji termed FER-1 (Tsuji et al, 1995), is a part of the ARE that activates transcription of the mouse ferritin H gene in response to hydrogen peroxide and phenolic electrophile compounds (Tsuji et al, 2000). Given the core ARE sequence TGACnnnGCA (Rushmore et al, 1991;Inamdar et al, 1996;Wasserman and Fahl, 1997b;Nioi et al, 2003), we identified an AP1-like (5 0 -TGACAAAGCA-3 0 ) followed by an AP1/NFE2 (5 0 -TGCTGAGTCA-3 0 ) sites located at À4.5 kbupstream region of the human ferritin H gene (Figure 3) and these two AP1 motifs are completely conserved between the human and mouse ferritin H genes (Tsuji et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear extract preparation, binding reactions, and electrophoretic mobility shifts were previously described [23]. Chromatin immunoprecipitation (ChIP) assays were performed according to a minor modification of Upstate Biology's ChIP assay protocol as previously described [14].…”
Section: Gel Retardation and Chip Assaysmentioning
confidence: 99%
“…The -4.8kb region of the mouse ferritin H promoter that was activated by rotenone contains an antioxidant responsive element (ARE), located 4.1kb upstream of the transcription start site [23]. Next we asked whether or not the ARE was involved in transcriptional activation of ferritin H by rotenone.…”
Section: The Ferritin H Gene Is Transcriptionally Activated By Rotenomentioning
confidence: 99%